2021
DOI: 10.3171/2020.9.jns202962
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the effects of low intensity focused ultrasound in a swine model of neuropathic pain

Abstract: OBJECTIVE The authors’ laboratory has previously demonstrated beneficial effects of noninvasive low intensity focused ultrasound (liFUS), targeted at the dorsal root ganglion (DRG), for reducing allodynia in rodent neuropathic pain models. However, in rats the DRG is 5 mm below the skin when approached laterally, while in humans the DRG is typically 5–8 cm deep. Here, using a modified liFUS probe, the authors demonstrated the feasibility of using external liFUS for modulation of antinociceptive responses in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…FUS is a noninvasive targeting therapy that uses a novel concave head to concentrate ultrasound energy into a range of millimeter diameters [ 31 ]. Unlike the thermal effects of high-intensity focused ultrasound (HIFU) [ 32 ], the biological effects of LIFU with regard to neuromodulation are primarily mechanical and can activate or inhibit neuronal activity by altering the state of mechanically sensitive ion channels embedded in cell membranes [ 33 , 34 ]. Over the past decade, ultrasound stimulation of neurons has shown numerous advantages over electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…FUS is a noninvasive targeting therapy that uses a novel concave head to concentrate ultrasound energy into a range of millimeter diameters [ 31 ]. Unlike the thermal effects of high-intensity focused ultrasound (HIFU) [ 32 ], the biological effects of LIFU with regard to neuromodulation are primarily mechanical and can activate or inhibit neuronal activity by altering the state of mechanically sensitive ion channels embedded in cell membranes [ 33 , 34 ]. Over the past decade, ultrasound stimulation of neurons has shown numerous advantages over electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This novel treatment represents a noninvasive alternative to current neuromodulatory treatments that involve the surgical placement of electric stimulators. 38 In the present study, we chose to measure neuropathic allodynia 7 days after CPNI induction. Rodent CPNI models based on VFF responses have shown that nerve ligation results in 180 days of neuropathic allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…This swine model worked well for our liFUS treatment, because the treatment alleviated neuropathic pain symptoms over a 1-month period. 38 However, measuring long-term change (such as during a 1-year period) would be difficult in this model, as animals weigh more than 300 kg at full size. 43 The novel swine CPNI model of neuropathic pain presented here is a modified version of the sciatic nerve injury surgery commonly used in rats.…”
Section: Discussionmentioning
confidence: 99%
“…[ 139 ] showed that ultrasound stimulation of the rat dorsal root ganglia increased mechanical and thermal sensory thresholds, and this improvement was more substantial in female rats [ 140 ]. They also demonstrated that ultrasound can alter pain behavior and allodynia in a porcine peroneal nerve-injury model [ 141 ]. This may be related to the improvement in the inflammatory response of the dorsal root ganglia via ultrasound stimulation [ 142 ].…”
Section: Ultrasound Brain Modulation and Possible Writingmentioning
confidence: 99%